Reef state and performance as indicators of cumulative impacts on coral reefs. (April 2021) - Castro-Sanguino, Carolina; Ortiz, Juan Carlos; Thompson, Angus; Wolff, Nicholas H.; Ferrari, Renata; Robson, Barbara; Magno-Canto, Marites M.; Puotinen, Marji; Fabricius, Katharina E.; Uthicke, Sven
Graphical abstract: Highlights: We assessed the contribution of multiple stressors to reef state and performance. Cumulative metrics of acute stressors were stronger predictors of reef health. Water quality impacts are better detected on reef performance than reef state. Temporal constraints in water quality data limit detectability of their effects. Metrics based on coral types can be better indicators than total coral metrics. Abstract: Coral bleaching, cyclones, outbreaks of crown-of-thorns seastar, and reduced water quality (WQ) threaten the health and resilience of coral reefs. The cumulative impacts from multiple acute and chronic stressors on "reef State " (i.e., total coral cover) and "reef Performance " (i.e., the deviation from expected rate of total coral cover increase) have rarely been assessed simultaneously, despite their management relevance. We evaluated the dynamics of coral cover (total and per morphological groups) in the Central and Southern Great Barrier Reef over 25 years, and identified and compared the main environmental drivers of State and Performance at the reef level (i.e. based on total coral cover) and per coral group . Using a combination of 25 environmental metrics that consider both the frequency and magnitude of impacts and their lagged effects, we find that the stressors that correlate with State differed from those correlating with Performance . Importantly, we demonstrate that WQ metrics better predict Performance than State . Further, inter-annual dynamics in WQ (here available for a subset of the data) improved the explanatory power of WQ metrics on Performance over long-term WQ averages. The lagged effects of cumulative acute stressors, and to a lesser extent poor water quality, correlated negatively with the Performance of some but not all coral groups. Tabular Acropora and branching non- Acropora were the most affected by water quality demonstrating that group-specific approaches aid in the interpretation of monitoring data and can be crucial for the detection of the impact of chronic pressures. We highlight the complexity of coral reef dynamics and the need of evaluating Performance metrics in order to prioritise local management interventions.